2019
DOI: 10.17557/tjfc.562634
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Aflatoxigenic Fungi on Peanut: For the Pre-Harvest Approach

Abstract: This study was carried out to determine the efficacy of different applications of a biopesticide for reduction of aflatoxin contamination in peanut. The biopesticide, afla-guard, delivers a nontoxigenic Aspergillus flavus to the field where it competes with naturally occurring toxigenic fungus. Biocontrol treatments included: (ı) soil application during sowing, (ıı) multiple application during sowing and 40 days after planting, (ııı) foliar application at 60 days after planting (ıv) control (untreated plots). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The results obtained from this study using Afla-Guard in corn showed parallelism with the results of studies conducted in different countries on peanuts and corn using Afla-Guard, and it was seen that it could successfully solve the AF problem on a field basis. ,,, In a study conducted in Turkey for the biological control of AF contamination in peanuts in 2015, Afla-Guard was shown to give effective results . In this study, the researchers reported that AF concentrations were generally quite low in treated samples (between 0.04 and 0.71 μg/kg), and AFs were reduced by 97 to 99% compared with the controls.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The results obtained from this study using Afla-Guard in corn showed parallelism with the results of studies conducted in different countries on peanuts and corn using Afla-Guard, and it was seen that it could successfully solve the AF problem on a field basis. ,,, In a study conducted in Turkey for the biological control of AF contamination in peanuts in 2015, Afla-Guard was shown to give effective results . In this study, the researchers reported that AF concentrations were generally quite low in treated samples (between 0.04 and 0.71 μg/kg), and AFs were reduced by 97 to 99% compared with the controls.…”
Section: Resultssupporting
confidence: 82%
“… 35 , 34 , 42 , 51 In a study conducted in Turkey for the biological control of AF contamination in peanuts in 2015, Afla-Guard was shown to give effective results. 52 In this study, the researchers reported that AF concentrations were generally quite low in treated samples (between 0.04 and 0.71 μg/kg), and AFs were reduced by 97 to 99% compared with the controls. Besides, in some studies, the researchers used locally non-aflatoxigenic A. flavus isolates to control AF contamination.…”
Section: Resultsmentioning
confidence: 77%
“…A second biocontrol product, Afla-guard ® , containing a different atoxigenic A. flavus isolate (NRRL21882) as an active ingredient, was registered with USEPA for use in maize and groundnut in the US [58]. The product Afla-guard ® is commercialized by Syngenta Crop Protection, Inc. (Greensboro, NC, USA) and has been used in experimental groundnut fields in Turkey [59].…”
Section: From Single To Multiple Isolatesmentioning
confidence: 99%
“…Synthetic pesticides are known have a negative effect to environment, human health, and natural enemies [6,7]. It has encouraged the researcher to developed of alternative non-synthetic pesticide to control chili diseases [8,9]. One of the alternative methods is developed a botanical pesticide [10,11].…”
Section: Introductionmentioning
confidence: 99%